Analisis Usahatani Padi Teknologi Hazton di Provinsi Kalimantan Barat (Studi Kasus: Desa Peniraman, Kecamatan Sungai Pinyuh, Kabupaten Mempawah) - Noviansyah, Yudha; Bariyah, Nurul (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2018)
In 2015, Ministry of Agriculture through Department of Agriculture of West Kalimantan did a productivity improvement program for paddy by adopting a new farming method which called the Hazton Technology. This research aimed to 1).determine and analize worthiness of Hazton Technology farming; and 2).determine and analize factors affecting paddy productions of Hazton Technology farming. The results shows that Hazton Technology is a worth paddy farming activity with the average score of R/C ratio as much as 2.69. Seeds amount variable and farming experiences have significant effects to paddy productions, while farming field and educational level do not have any significant effects to paddy productions.